Unbinding of alpha chain of hemoglobin in sickle and normal structures - Jhulan Powrel; Rajendra Prasad Koirala; Narayan Prasad Adhikari (Journal of Physics Communications)
Sickle cell disease, a genetic disorder, is caused by a mutation of glutamic acid into valine in β chain of hemoglobin at the sixth residue, resulting in structural change of the entire hemoglobin molecule into a sickle shape. We investigated the atomic level interaction between the α chain (chain A) and the remaining three chains to identify the structural modification in sickle hemoglobin using the molecular dynamics simulations. Hydrogen bonding, solvent accessible surface area (SASA), hydrophobic interactions, salt bridges of sickle and normal hemoglobin have been estimated. The estimated parameters from sickle hemoglobin is compared to normal hemoglobin structure. Steered Molecular Dynamics (SMD) has been utilized to estimate the force required in breaking hydrogen bonds in given chains. The SMD simulations at different pulling velocities show that the decoupling force depends on value of pulling force. This relation is linear, 6780 pN to 12345 pN with pulling velocities of 0.00020nm/ps to 0.00040nm/ps in sickle hemoglobin. Much higher force of 8738 pN to 16557 pN in normal is required in normal hemoglobin with same spring constants values from k = 500 to 1100 kcal mol ^−1 nm ^−2 and same pulling velocities.